A Qualitative Research on the Use of Fashion for Public Relations Practitioners as a Presentation of Self-image - Rachmat Kriyantono; Farikha Rakhmawati (Soshum: Jurnal Sosial dan Humaniora, 2020)
ABSTRACT ___________________________________________________________________ The research aims to uncover the dominance of hidden ideology in the practice of fashion that is used public relations practitioners in Indonesia. This research becomes important to awaken public relations practitioners, especially women, that fashion style used unconsciously is still influenced by patriarchal culture, capitalism, and hedonism. Researchers want to know and prove that the fashion public relations in Indonesia still marginalized and feminized in the selection of fashion. In addition, the researcher aims to formulate the characteristics of public relations fashion in accordance with the culture of Eastern Indonesia. The method used in this research is a qualitative method to explore the fashion used by public relations practitioners. Through data retrieval techniques, in-depth interviews and documentation, research was conducted on 29 public relations practitioners in Indonesia with convenient technique. Using a critical approach, researchers try to uncover the motives and ideologies that influence public relations practitioners in fashion using a feminist perspective. The results of this research indicate that the fashion used by public relations practitioners in Indonesia is influenced by the culture of eastern Indonesia, patriarchal culture, and capitalism. Indonesian public relations practitioners tend to use ingratiation strategy as a presentation of self image through fashion to gain public attention. In addition, research findings show that fashion is used to represent a positive image of the organization and simplify communication practice. The fashion used by public relations practitioners in Indonesia is influenced by the eastern culture and perspectives of Indonesia. Public relations practitioners in Indonesia prefer Indonesian culture such as traditional clothes, kebaya (Javanese blouse), batik, and applying the values ​​of politeness and nationalism in a fashion though much exposed to western culture. This is one of the evidence by the rise of hijab fashion trends in Indonesia that changed the paradigm of public relations practitioners who prioritize sexual appeal. © 2019 Politeknik Negeri Bali